2001
DOI: 10.1074/jbc.m008449200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Conservation of Neurotropism-associated VspA within the Variable Borrelia Vsp-OspC Lipoprotein Family

Abstract: Vsp surface lipoproteins are serotype-defining antigens of relapsing fever spirochetes that undergo multiphasic antigenic variation to avoid the immune response. One of these proteins, VspA of Borrelia turicatae, is also associated with neurotropism in infected mice. Vsp proteins are highly polymorphic in sequence, which may relate to their specific antibody reactivities and host cell interactions. To determine whether sequence variations affect protein structure, we compared B. turicatae VspA with three relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 65 publications
3
60
0
Order By: Relevance
“…For this we injected intraperitoneally new groups of uninfected or Bt1-infected RAG1 Ϫ/Ϫ mice simultaneously with 100 g/kg of Eu-albumin and 100 g/kg of Sm-LVsp1 to determine whether the presence of Eu-LVsp1 increased the dissemination to the brain of Eu-albumin, which has a molecular weight three times larger than that of LVsp1. 21 The results showed that the dissemination of Eu-albumin to brain did not change in the presence of Eu-LVsp1 (Supplemental Figure 4, see http://ajp.amjpathol.org; P ϭ NS). We concluded that the increase in dissemination of LVsp1 to the brain as a result of infection was unlikely to be explained by nonspecific opening of the BBB.…”
Section: Bacterial Infection Increases the Dissemination Of Lvsp1 Intmentioning
confidence: 83%
See 1 more Smart Citation
“…For this we injected intraperitoneally new groups of uninfected or Bt1-infected RAG1 Ϫ/Ϫ mice simultaneously with 100 g/kg of Eu-albumin and 100 g/kg of Sm-LVsp1 to determine whether the presence of Eu-LVsp1 increased the dissemination to the brain of Eu-albumin, which has a molecular weight three times larger than that of LVsp1. 21 The results showed that the dissemination of Eu-albumin to brain did not change in the presence of Eu-LVsp1 (Supplemental Figure 4, see http://ajp.amjpathol.org; P ϭ NS). We concluded that the increase in dissemination of LVsp1 to the brain as a result of infection was unlikely to be explained by nonspecific opening of the BBB.…”
Section: Bacterial Infection Increases the Dissemination Of Lvsp1 Intmentioning
confidence: 83%
“…The following proteins were used in this study: (1) LVsp1 and LVsp2, the major outer membrane lipoproteins of serotypes 1 (Bt1) and 2 (Bt2), respectively, of the relapsing fever spirochete B. turicatae; they were prepared by detergent extraction from cultures of Bt1 or Bt2 spirochetes as before 20 ; (2) rVsp1 was kindly provided by Wolfram Zuckert, PhD (University of Kansas Medical Center) 21 ; and (3) mouse albumin was purchased from Sigma (St. Louis, MO, category number A1056). Protein purity was confirmed by SDS-polyacrylamide gel electrophoresis (Supplemental Figure 1, see http://ajp.amjpathol.org) and by Western blot with monoclonal antibodies anti Vsp1 (1H12) or anti Vsp2 (5F12) 20,22 (not shown).…”
Section: Protein Labeling and Purificationmentioning
confidence: 99%
“…Analytical ultracentrifugation and gel filtration chromatography experiments were performed in our laboratories in analogy to analyses of other surface proteins (19) and indicate that recombinant VlsE1 is primarily monomeric in solution (data not shown). In the crystal structure, the interface between neighboring VlsE1 molecules in the asymmetric unit buries ϳ13% of the accessible surface area of each monomer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The positions of the sequence motifs are approximately to scale and their order is according to occurrence in respective alleles. Also shown are the relative positions of predicted ␣-helices in the mature proteins (27). Two of the repeats, A and C, occur first in the sequence encoding the signal peptide.…”
Section: Figmentioning
confidence: 99%